The geography of investor attention - Stefano Mengoli; Marco Pagano; Pierpaolo Pattitoni (Goethe University Frankfurt, Center for Financial Studies (CFS), 2021)
Retail investors pay over twice as much attention to local companies than non-local ones, based on Google searches. News volume and volatility amplify this attention gap. Attention appears causally related to perceived proximity: first, acquisition by a nonlocal company is associated with less attention by locals, and more by nonlocals close to the acquirer; second, COVID-19 travel restrictions correlate with a drop in relative attention to nonlocal companies, especially in locations with fewer flights after the outbreak. Finally, local attention predicts volatility, bid-ask spreads and nonlocal attention, not viceversa. These findings are consistent with local investors having an information-processing advantage.
Keywords: D83; G11; G12; G14; G50; L86; R32; 330; attention; retail investors; local investors; distance; news; liquidity; volatility